Profiling MPI applications with mixed instrumentation - Grosclaude, Eduardo (2010)
Our research project intends to build knowledge about HPC problems to be able to help local researchers. In order to advise users in choosing parallel machines to run their applications, we want to establish a general methodology, requiring as shallow information as possible, to characterize parallel applications. To draw a profile of a closed, message-passing application, we look for convenient tools for inspection on the distribution of communication primitives. We show a feasible way to do black-box instrumentation of closed MPI applications.